THE INFLUENCE OF PROGRESSIVE MUSCLE RELAXATION TECHNIQUES ON DEPRESSION LEVEL OF CRONIC KIDNEY DISEASE PATIENT UNDERGOING HEMODIALYSIS THERAPY - ifa roifah; Amar Akbar (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2017)
Hemodialysis is a renal replacement therapy for patients with cronic renal disease who are decline of renal fuction. The complex therapy and physical condition of chronic kidney disease and hemodialysis patient involve a severe stressor that lead to depression. Progressive muscle relaxation technique is one of nonpharmacoloical therapies that treat depression. This research aimed to prove the influence of progressive muscle relaxation technique to changes in depression level in cronic kidney disease with hemodialysis in Dr. WahidinSudiroHusodoMojokertohospital. In this research design used is Quasy experiment with pre-test post-test control group design. Sample of 30 people were taken by simple random sampling. 15 people from experimental group were given routine progressive muscle relaxation technique in 2 times a day of the week and 15 people from control group were given not routine progressive muscle relaxation techniques in 2 day one time in a week . The research instrument was Beck Depression Inventory. Wilcoxon Signed Rank Test shows that p value (0.001) < Î± (0.05), so it is accepted that there is an effect of progressive muscle relaxation on the depression level of cronic kidney disease patient undergoing hemodialysis. To test the U-Mann Whitney shows that p value (0.005) < Î± (0.05), so that H0 is rejected it means there is different of the channge depression level between experiment group and the control group.this therapy can increase the production of melatonin and serotonin, reduce stress hormone cortisol. PMR also, lowering the muscle tension ,do make positive thinking so, throught that is influence to decrease in depression level. Routine muscle relaxationdistractify the stressor everyday in training.